PERUBAHAN STATUS BADAN HUKUM PERUMDA MENJADI PERSERODA DALAM RANGKA KEMANDIRIAN DIREKSI:: Studi Atas PDAM - Romanus Pangeran Bangsawan Purba (to-ra, 2020)
The choice of legal entity form in running a company will determine how the relationship between the individuals in the company. The legal entity forms of Regional Public Company and Regional Limited Company are two forms of legal entity that are recognized as Regional Government Owned Enterprises based on Law Number 23 of 2014. The relationship between capital owners / shareholders and management of both types of legal entities will influence the determination of policies in running the company. How business processes in both forms of legal entity will determine how to achieve company goals in accordance with the company's Articles of Association.